Prenylated isoflavones from the stem bark of Erythrina sacleuxii. (August 2018) - Ombito, Japheth O.; Majinda, Runner R.T.; Masesane, Ishmael B.; Bojase, Gomotsang; Schüffler, Anja; Opatz, Till
Graphical abstract: Highlights: Two new prenylated isoflavones, named erysacleuxin A and B were isolated from the stem bark of Erythrina sacleuxii Hua. Eight known compounds were isolated from the stem bark of Erythrina sacleuxii Hua. The structures were determined based on spectroscopic and spectrometric data. Antifungal activity of the isolated compounds against Pyricularia oryzae and Rhizomucor miehei was evaluated. Abstract: Two new prenylated isoflavones, named erysacleuxin A (1 ) and B (2 ), along with eight known compounds, biochanin A (3 ), 5′-(3-methylbut-2-enyl)pratensein (4 ), 7-demethylrobustigenin (5 ), 3′-(3-methylbut-2-enyl)biochanin A (6 ) abyssinone V-4′-methyl ether (7 ), sigmoidin E (8 ), erythrinasinate (9 ), and burtinone (10 ) were isolated from the stem bark of Erythrina sacleuxii Hua (Leguminosae). The structures were determined based on spectroscopic and spectrometric data. All isolated compounds were evaluated for antifungal activity against Botrytis cinerea, Candida albicans, Eremothecium coryli, Penicillium notatum, Pyricularia oryzae, and Rhizomucor miehei with compounds 3, 4 and 6 showing weak to moderate activity against P. oryzae and R. miehei .